Effect of Hepatocellular Carcinoma on Mortality Among Individuals With Hepatitis B or Hepatitis C Infection in New York City, 2001–2012. (16th June 2018) - Moore, Miranda S; Bocour, Angelica; Tran, Olivia C; Qiao, Baozhen; Schymura, Maria J; Laraque, Fabienne; Winters, Ann
Abstract: Background: Hepatocellular carcinoma (HCC) is a complication of chronic hepatitis B and C virus (HBV and HCV) infection. New York City (NYC) has a high prevalence of HBV and HCV, and infected persons likely face increased mortality from HCC and other causes. We describe the mortality profile of NYC residents with HBV or HCV, emphasizing the contributions of HCC and HIV coinfection. Methods:  Two existing data sets were combined to examine all individuals diagnosed with HBV or HCV in NYC first reported to the Health Department during 2001–2012 and their HCC, HIV, and vital status. Logistic regression was used to calculate the odds of HCC diagnosis by viral hepatitis status, whereas Cox proportional hazard regression was used to estimate the hazard of death by HCC/HIV status. Results: In total, 120 952 and 127 933 individuals were diagnosed with HBV or HCV, respectively. HCV-infected individuals had 17% higher odds of HCC diagnosis than HBV-infected individuals and 3.2 times higher odds of HIV coinfection. Those with HCV were twice as likely to die during the study period (adjusted hazard ratio, 2.04; 95% confidence interval, 1.96–2.12). The risk of death increased for those with HIV or HCC and was highest for those with both conditions. Conclusions: HCC and HIV represent substantial risks to survival for both HBV- and HCV-infected individuals. Individuals with HBV need close monitoring and treatment, when indicated, and routine HCC screening. Those with HCV need increased, timely access to curative medications before developing liver disease.